Injectable platelet-rich fibrin promotes proliferation and trichogenic inductivity of dermal papilla cells through activating TGF-β/Smad signaling pathway: i-PRF activates DPCs by TGF-β/Smad - Xu, Kai; Deng, Xueqin; Ye, Minmin; Cheng, Baolin; Zhu, Lili; Ding, Chunming; Hou, Tuanjie (Cellular and Molecular Biology, 2024)
Dermal papilla cell (DPC) belongs to a specialized mesenchymal stem cell for hair follicle regeneration. Maintaining the ability of DPCs to stimulate hair in vitro culture is important for hair follicle morphogenesis and regeneration. As the third generation of platelet concentrate, injectable platelet-rich fibrin (i-PRF) is a novel biomaterial containing many growth factors and showing promising effects on tissue reconstruction. We aimed to explore the influences of i-PRF on the proliferative, migratory, as well as trichogenic ability of DPCs and compared the effects of i-PRF and platelet-rich plasma (PRP), the first generation of platelet concentrate. Both PRP and i-PRF facilitated DPCs proliferation, and migration, along with trichogenic inductivity as well as stimulated the TGF-β/Smad pathway, while the impacts of i-PRF were more significant than PRP. A small molecule inhibitor of TGF-beta receptor I, Galunisertib, was also applied to treat DPCs, and it rescued the impacts of i-PRF on the proliferative, migratory, trichogenic inductivity, and proteins-associated with TGF-β/Smad pathway in DPCs. These findings revealed that i-PRF had better effects than PRP in enhancing the proliferative, migratory, and hair-inducing abilities of DPCs by the TGF-β/Smad pathway, which indicated the beneficial role of i-PRF in hair follicle regeneration.